Exploration Of The Value Of Islam-Based Multicultural Education In Local Wisdom Traditions National Culture Adab - Hamdanah Hamdanah; Muslimah Muslimah; Hafidzatul Muslimah (At-Tarbiyat, 2023)
Multicultural values in Nasi Adab culture in Kotawaringin Barat district are the only artifacts that have not been explored in taking the fundamental values from their contents. This study explores the character values contained in the Nasi Adab culture, focusing on the multicultural values that are traditionalized by the community and the West Kotawaringin district government. This study uses a qualitative method with purposive sampling data collection techniques through participant observation and in-depth interviews. Validation of data using triangulation techniques and extending observations to several data sources. Meanwhile, the data processing and analysis technique used the Nvivo-12 application. The findings of this study are that local wisdom in the form of Nasi Adab culture can become the glue of community unity. This is expressed through character values in forming a harmonious and peaceful life against differences in ethnicity, culture, and religion. In addition, the value of tolerance is shown by the existence of public awareness about diversity in differences. This awareness raises the value of multiculturalism through mutual acceptance of differences from diversity to become a common strength. Thus, Nasi Adab culture contains values that eliminate the stigma of religious and cultural sensitivity that occurs in social life in the West Kotawaringin district